2012
DOI: 10.1016/j.juro.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Optimizing Testosterone Before Microdissection Testicular Sperm Extraction in Men with Nonobstructive Azoospermia

Abstract: Men with nonobstructive azoospermia and hypogonadism often respond to hormonal therapy with an increase in testosterone levels, but neither baseline testosterone level nor response to hormonal therapy appears to affect overall sperm retrieval, clinical pregnancy or live birth rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 14 publications
3
94
1
Order By: Relevance
“…Reifsnyder et al also reported a partial effect of testosterone optimization on micro-TESE outcomes following treatment with clomiphene citrate, hCG or aromatase inhibitors. Ramasamy et al reported that Klinefelter syndrome, men with low baseline testosterone levels who responded to medical therapy to enhance testosterone production with resultant testosterone levels greater than 250 ng/dL had a 77 % chance of sperm retrieval versus 55 % for men who did not respond [64]. These observations suggest that men who can produce increased testosterone levels may also produce increased levels of the other growth factors secreted from Leydig and Sertoli cells [48].…”
Section: Fsh Stimulation Of Sertoli Cellsmentioning
confidence: 99%
“…Reifsnyder et al also reported a partial effect of testosterone optimization on micro-TESE outcomes following treatment with clomiphene citrate, hCG or aromatase inhibitors. Ramasamy et al reported that Klinefelter syndrome, men with low baseline testosterone levels who responded to medical therapy to enhance testosterone production with resultant testosterone levels greater than 250 ng/dL had a 77 % chance of sperm retrieval versus 55 % for men who did not respond [64]. These observations suggest that men who can produce increased testosterone levels may also produce increased levels of the other growth factors secreted from Leydig and Sertoli cells [48].…”
Section: Fsh Stimulation Of Sertoli Cellsmentioning
confidence: 99%
“…Uncontrolled studies have reported moderate positive effects on sperm retrieval rates in patients with nonobstructive azoospermia (NOA) (78,79). However, controversy exists and a very recent study on 1054 men with NOA found that neither baseline testosterone nor the response to preoperation hormonal therapy had any effect on overall sperm retrieval, clinical pregnancy, or live birth rates (80).…”
Section: Preoperation Hormonal Therapymentioning
confidence: 99%
“…However, the lack of useful predictive biomarkers suggestive for successful sperm retrieval at microTESE in NOA men still represents a relevant gap with a very negative return for the patient. Indeed, no significant association has been found between microTESE sperm retrieval outcomes and (i) preoperative testicular volume, (ii) baseline follicular stimulating hormone (FSH) levels, (iii) basal level of Testosterone (T) or increased T level following treatments with aromatase inhibitors, clomiphene citrate or human chorionic gonadotropin 13,14 . Thereof, we sought to identify novel and user-friendly prognostic factors reliably predicting surgical outcomes in iNOA men in the real-life setting.…”
mentioning
confidence: 99%